2020
DOI: 10.1016/j.heliyon.2020.e03622
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-elastic behaviour of carbon-fiber reinforced polymer and the effect of adding nanoparticles at elevated heat intensity

Abstract: Thermal stress development in materials could lead to structural failure in engineering applications. Carbon-fiber reinforced polymer composite (CFRP) have gained wide acceptance in the manufacturing industry. However, its thermo-elastic behaviour at elevated temperatures still remains an open question. Heat transfer analysis coupled with material layer-wise arrangement technique of the CFRP was implemented to investigate the thermo-elastic behaviour of these composites. A finite element model (FEM) was built … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A numerical investigation of thermo-elastic behaviour on CFRP at elevated temperatures has been studied by Ejeh et al [34] using heat transfer analysis coupled with material layer-wise arrangement technique. The results revealed that thermal stresses are intense along fiber-direction of the composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical investigation of thermo-elastic behaviour on CFRP at elevated temperatures has been studied by Ejeh et al [34] using heat transfer analysis coupled with material layer-wise arrangement technique. The results revealed that thermal stresses are intense along fiber-direction of the composite laminates.…”
Section: Introductionmentioning
confidence: 99%